La incidencia del crédito en la producción del sector agrícola de la cabecera cantonal del Cantón Catamayo, Provincia de Loja, año 2014 - Lapo Alulima, Yesenia Elizabeth (2016)
The agricultural sector has great economic importance to the cantonal head of the canton Catamayo, since it constitutes the main source of income for much of the population; therefore, the introduction of resources to its growth is necessary; as there is still a segment of producers who have not agreed to significant sources of funding that enhance agricultural production and thus obtain the corresponding benefit. Faced with this problem it has been conducted research "THE IMPACT OF CREDIT IN AGRICULTURAL PRODUCTION SECTOR CANTONAL CATAMAYO head of the canton, province of Loja, 2014," the same as aimed; determine the share of agricultural credit in the cantonal head of the canton Catamayo, Loja province, 2014, through a descriptive study to determine its impact on production. This research involved the agricultural producers of the cantonal head of the canton Catamayo, taking as example to 65 farmers. Secondary information was provided mainly by the Superintendency of Banks Superintendency of popular and solidarity economy and Central Bank of Ecuador. Primary data were obtained from surveys directed to farmers through a questionnaire, which made it possible to obtain the information necessary for the fulfillment of the objectives and a time to draw conclusions and recommendations. Once applied the methodology, it was concluded that the cantonal head of the canton Catamayo, 2014, 62% of farmers received funding and invested mainly in crop production and purchase of inputs; This group of farmers receiving loans, 85% scored higher positive returns 50%; ie revenues from sales, managed to cover production costs, indicating a positive credit impact on agricultural production. Keywords: agricultural credit, production, benefit, throwput, Catamayo, Loja province.